Transabdominal bilateral adrenalectomy for metastatic breast carcinoma. - Benson, E. A. (Royal College of Surgeons of England, 1979)
A case is made for the more general adoption of the transabdominal approach to the adrenal glands as this has obvious advantages over bilateral loin incisions.